2016
DOI: 10.1155/2016/2718421
|View full text |Cite
|
Sign up to set email alerts
|

Bilaterally Symmetrical Lower Extremity Compartment Syndrome following Massive Transfusion

Abstract: Compartment syndrome is a serious condition characterized by raised intracompartmental pressure, which develops following trauma. Well leg compartment syndrome (WLCS) is a term reserved for compartment syndrome in a nontraumatic setting, usually resulting from prolonged lithotomy position during surgery. In literature, 8 cases have been reported regarding well leg compartment syndrome in a supine position and bilateral symmetrical involvement was observed in only 2 cases. In WLCS etiology, lengthy surgery, len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…The present study also revealed that the central soleus muscle is most frequently subjected to the pressure load. Postoperative incidence of WLCS and DVT are most often associated with the soleus muscle, and pressure loading in this area must be considered during rectal surgeries [ 13 , 25 , 26 ]. However, as pressure application on the soleus muscle is not avoidable when using lithotomy stirrups, it is important to improve the quality of the stirrups to reduce the pressure load on this muscle.…”
Section: Discussionmentioning
confidence: 99%
“…The present study also revealed that the central soleus muscle is most frequently subjected to the pressure load. Postoperative incidence of WLCS and DVT are most often associated with the soleus muscle, and pressure loading in this area must be considered during rectal surgeries [ 13 , 25 , 26 ]. However, as pressure application on the soleus muscle is not avoidable when using lithotomy stirrups, it is important to improve the quality of the stirrups to reduce the pressure load on this muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Highly related codes were presented adjacent to each other in Tables 3 through 10 and subtotaled. All 524 diagnoses in the tables met one of the following criteria 32–85 :…”
Section: Methodsmentioning
confidence: 99%